Employment of Hotel Classification to Increase Tourist Demand in the Holy Province of Karbala Period 2010-2017 - Al-Sammarraie, Maha Abdulsattar; Jaafar Azeez, L. Salam; Dheyaa Salman, A.l. Haider (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT Hotels are one of the main pillars in the success of the process of tourist activities in countries that have a variety of tourist elements. The variety and classification of hotels differentiates the levels of quality in services. In the case of the sacred province of Karbala, a hotel classification with a variety of quality levels and stars was adopted to express the diversity of services offered within the country's conditions and tourist demand..